The Effect Of Education Level, Accounting Understanding, Work Motivation, And Business Size On The Preparation Of UMKM Financial Reports Based On EMKM SAK (Case Study Of Culinary Umkm In Medan City) - Triya Vebrianty; Nina Andriany Nasution; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to determine the effect of the Influence of Education Level, Accounting Understanding, Work Motivation, and Business Size on the Preparation of MSME Financial Reports Based on SAK EMKM (Case Study of Culinary MSMEs in Medan City). This study uses a quantitative descriptive approach. Sample selection was carried out by purposive sampling, based on certain criteria. Primary data were collected through interviews and questionnaires. Data analysis was carried out using Multiple Linear Regression Analysis with the help of SPSS software. The results of the study indicate that partially Accounting Understanding and Work Motivation have a positive and significant effect on the preparation of MSME financial reports based on SAK EMKM. While the Level of Education and Business Size partially do not affect the preparation of MSME financial reports based on SAK EMKM. Simultaneously, Accounting Understanding, Work Motivation, Education Level and Business Size have a positive and significant effect on the preparation of MSME financial reports based on SAK EM